2011
DOI: 10.1093/infdis/jir491
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Migration and Domestic Transmission in the Spread of HIV-1 Non-B Subtypes in Switzerland

Abstract: Of all non-B infections diagnosed in Switzerland, <25% could be prevented by domestic interventions. Awareness should be raised among immigrants and Swiss individuals with partners from high prevalence countries to contain the spread of non-B subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
66
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 18 publications
9
66
1
1
Order By: Relevance
“…The present work confirms CRF02_AG as the prevalent circulating recombinant form in our region, as well as in several European countries (González-Alba et al, 2011;von Wyl et al, 2011;Yebra et al, 2012), in contrast to that observed in the northern part of Italy where subtype F1 is the most prevalent non-B clade (Lai et al, 2010), mirroring the extensive influx of immigrants from Romania, an European country with a massive prevalence of subtype F1 HIV-1 infections .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present work confirms CRF02_AG as the prevalent circulating recombinant form in our region, as well as in several European countries (González-Alba et al, 2011;von Wyl et al, 2011;Yebra et al, 2012), in contrast to that observed in the northern part of Italy where subtype F1 is the most prevalent non-B clade (Lai et al, 2010), mirroring the extensive influx of immigrants from Romania, an European country with a massive prevalence of subtype F1 HIV-1 infections .…”
Section: Discussionsupporting
confidence: 89%
“…Brazil, the Caribbean, and Thailand) could likely be responsible for the entry of an array of group M subtypes into formerly subtype B-restricted geographic areas and, consequently, contributing for the changing profile of the local HIV epidemiology in host countries (Rice et al, 2012). As similarly reported in other studies in Italy (Lai et al, 2010) and elsewhere (Hawke et al, 2012;von Wyl et al, 2011), in the present paper, the totality of non-B infections among immigrant subjects correlate to heterosexual transmission, while non-B infections in homosexual individuals were exclusively found in Italian-born patients. Of note, native Italians who were infected with HIV-1 non-B strains mainly harboured URFs while known CRFs/subtypes were found only in a minority group of subjects.…”
Section: Discussionsupporting
confidence: 55%
“…It is important to gain a further understanding on the causes underlying this difference, also in light of the evidence supporting a recent increase in infections with non-B HIV-1 subtypes in several western European countries (15)(16)(17)44). In this study, we analyzed 289 HIV-1-infected individuals from Minho province, Portugal.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the studied ethnic groups may be due to a range of factors. For example, infection characteristics in our cohort differed among ethnicities: nonwhite participants acquired HIV-1 more frequently outside of Switzerland, their infection was detected later and they showed higher frequencies of females and heterosexual transmissions 36,37 (Supplementary Table 12). Controlling for confounding parameters, our analysis confirmed, however, that black ethnicity is associated with higher bnAb frequencies independently of influences from all other probed variables, including the duration of infection (Supplementary Table 11).…”
Section: Defining Determinants Of Bnab Developmentmentioning
confidence: 99%